Revising Biomimetics: Opportunities and Ambiguities in the Bioinspired Design Approach - Carla Langella; Amilton J. V. Arruda; Carmelo Di Bartolo (DIID, 2022)
The paper aims to propose an overview of biomimetic design, exploring its features from a methodological and critical point of view, highlighting its potential but also its limits, ambiguities, risks, and obscurities. Critical interpretations of biomimetic design are presented through a method based on comparative literature review. This was filtered by several crucial questions aimed at highlighting the effectiveness and value of design approaches based on the observation and emulation of nature in our current historical period. Semantic choices, market impact, efficiency of methods, interdisciplinary collaboration, ethical and environmental consequences are some of the issues analysed. These themes have been selected taking into consideration open and unresolved matters within the international state of the art, in order to trace possible evolutionary strategies for the biomimetic approach, relating it to the current social, economic, political and technological scenario.